Library user education and use of information resources by students of Federal College of Agriculture Ibadan, Oyo State - Kehinde, R. Bolanle; Adeyeye, Sophia Vivian (Access: An International Journal of Nepal Library Association, 2023)
In spite of provision of information resources to suit the educational needs of students and scholars, use of information resources (IR) by students of higher institution of learning can largely be under-utilized. Hence, this study investigated the influence of library user education on use of information resources by students of Federal Colleges of Agriculture Ibadan, Oyo State. Descriptive research design was adopted. Population consists of eight hundred and ten (810) ND 1 and ND 2 students of Federal Colleges of Agriculture Oyo State. Proportionate Sampling technique was adopted as the sampling technique for this study as well. 265 respondents served as the sample size for this study. Data collected was analyzed using descriptive and inferential statistics. Findings revealed that LUE had significant influence on use of IR (Adj. R2 =0.027; p = 0.009). It was recommended that Librarians have to adopt library orientation, on-line instruction and course-related instruction as form of library user education to promote massive use of their information resources.